Napoleon Dynamite - Coon, Jeremy; Wyatt, Chris, 1975-; Covel, Sean, 1976-; Hess, Jared, 1979-; Hess, Jerusha; Heder, Jon, 1978-; Gries, Jon, 1957-; Ruell, Aaron; Ramirez, Efren, 1973-; Majorino, Tina, 1985-; Bader, Diedrich, 1966-; Powell, Munn.; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2004)
Napoleon is a new kind of hero, complete with a tight red 'fro, sweet moon boots, and skills that can't be topped. Napoleon spends his days drawing mythical beasts, duking it out with his older brother, Kip, and trying to avoid his scheming Uncle Rico. When two new friends enter Napoleon's life - shy Deb and mustachioed Pedro - the trio launches a campaign to elect Pedro for class president and make the student body's wildest dreams come true. But if Pedro is to beat stuck-up Summer, Napoleon will have to unleash his own secret weapon.
Side A. Full screen version -- side B. Widescreen version.
Double sided, single layer.
Special features: full-length audio commentary by director/co-writer Jared Hess, actor Jon Heder, and producer Jeremy Coon; deleted scenes with audio commentary by director/co-writer Jared Hess, actor Jon Heder and producer Jeremy Coon; featurette; promo spots; still gallery.
Casting by Jory Weitz ; music by John Swihart ; editor, Jeremy Coon ; production designer, Cory Lorenzen ; director of photography, Munn Powell.
Jon Heder, Jon Gries, Aaron Ruell, Efren Ramirez, Tina Majorino with Diedrich Bader.
MPAA rating: PG; for thematic elements and language.
DVD; NTSC; region 1, side 1: widescreen (1.85:1), side 2: full screen (1.33:1) presentations; Dolby Digital 5.1 surround.
Keywords: High school students -- Drama; High school students -- Political activity -- Drama; Student government -- Elections -- Drama; Comedy films; Feature films; Fiction films; Video recordings for the hearing impaired